Understanding Sustainability through Traditional Maasai Pastoral Systems in Southern Kenya - Impink, Emma; Gaynor, Kaitlyn M. (Consilience, 2010)
In the developed world, we tend to think of sustainability as a newly articulated solution to challenges of environmental resource degradation and issues of social and economic injustice. However, pastoralism, as traditionally practiced by the Maasai of southern Kenya, is intimately tied to the land and responds to climatic variation of the region. As a result of a shift toward privatization of land tenure, traditional pastoral systems are no longer viable. While studying abroad with The School For Field Studies, we became aware of the struggle many Maasai face as they attempt to continue pastoralism in an increasingly hostile environment. Ultimately, development efforts in the region should focus not on implementing exogenous concepts of ‘sustainability’ but rather on supporting and adapting systems that are already in place.